Implementation of The Law Principles of Good Corporate Governance in Indonesian Village-Owned Enterprise (BUMDes) - Sri Winarsi; Oemar Moechthar (Yuridika, 2020)
Based on Law No. 6/2014 concerning Village in Indonesia, in order to increase the utilization of all economic potentials, economic institutions, as well as natural resources and human resources in an effort to improve welfare of the village communities, the village government can form village-owned enterprise (BUMDes). In its practice, implementation of the BUMDes management in several regions is not fully optimized, so that many cases of corruption were found. Thus, good governance practices are needed for optimizing the management of BUMDes to improve the livelihoods of the village. The methods used in this research is statute approach, conceptual approach, and case approach. The conclusions obtained in this research are directed to contribute to the concepts of strengthening the national law related to the management of BUMDes. Hopefully, it can strengthen the village's economy and reduce the level of corruption in Indonesia that is detrimental for the village.